基于Pro/E和ADAMS的2K-V型减速机的运动学仿真 - 张春亮; 李充宁; 戚厚军 (Jixie chuandong)
By means of virtual prototyping technology,a precise virtual digital prototype of 2K-V reducer has been built based on Pro/E and Adams.The application of virtual link is successful in solving the problem of defining the mechanism and gear coupling of 2K-V reducer.The modeling process and simulation parameters are introduced in detail.The simulation expresses real kinematical process.The components’ velocity is real-timely measured during kinematical simulation.Simulation results demonstrate the correctness of model building and simulation process.